Direito à água: por uma constituição global em defesa de bens fundamentais - Casagrande, Vanessa Ramos (2023)
This work, inserted in the Research Line "Constitutional Jurisdiction and Democracy", its purpose is to study the need for a Constitution Global to protect water as a fundamental good. In the development of In this study, the hypothetical-deductive method was considered, which allows the researcher can go from the known to the unknown, and also the hermeneutic method, with the aim of better understanding doctrine and legislation. As regards procedural techniques, bibliographic and documentary techniques were used, with support in normative instruments of the Brazilian legal system, and sources bibliographical, with a qualitative approach. In this context, the first chapter dedicates the study of constitutionalism, its evolution, the issue of sovereignty and the globalization. It also analyzes the crisis that affects the current model of constitutionalism and the issue of transconstitutionality, in addition to verifying the possible model for the constitutionalism of the future, based on a multilevel and guaranteeist scheme. The study of the second chapter covers fundamental rights and the corresponding fundamental goods based on Luigi Ferrajoli's theory. Finally, the third chapter recognizes water as a fundamental good and demonstrates regulatory insufficiency current legal framework to guarantee everyone's access to drinking water, concluding that only a global constitution is capable of establishing the necessary protection.